Beneficial effect of growing Melastoma malabathricum with the addition of bamboo biochar and EDTA in removing soil heavy metal(loid)s contamination - Saberi, Norshahida; Halmi, Mohd Izuan Effendi; Zakaria, Norazua; Ahmad Hamdani, Muhammad Saiful; Khandaker, Moneruzzaman; Yong, Jean Wan Hong; Mahmud, Khairil (Taylor and Francis, 2025)
A study was conducted to investigate the synergistic effect of growing Melastoma malabathricum with the addition of bamboo biochar (BB) and ethylenediaminetetraacetic acid (EDTA) in reducing soil heavy metal(loid)s. Soils from the Chini watershed, a Man and Biosphere Reserve by UNESCO, which faces mining activities, were collected, analyzed, and used for a greenhouse experiment. The experiment was set up with five treatments by growing M. malabathricum with BB and/or EDTA, a control, and blank (organic soil). M. malabathricum demonstrated robust growth throughout the experiment, displaying no common phytotoxic symptoms when growing with the contaminated soil. Applying BB and EDTA gradually increased 50% of plant height and biomass and improved the uptake of heavy metal(loid)s: Fe:42%, As:62%, Pb:83%, Cr: 88%, and Al: 5%. This treatment also achieved the highest phytoextraction efficiency, with reductions of heavy metal(loid)s in the soil (up to 33%) compared to the control. Growing M. malabathricum with BB and EDTA additions was a promising method in reducing soil heavy metal(loid)s, making it beneficial for restoration efforts at ex-mining sites, particularly at the Chini watershed in the future.